Security in cyber-physical systems: challenges and solutions. (2017) - Zhou, Keliang; Liu, Taigang; Liang, Ling
Cyber-physical systems (CPSs), which integrate physical components and computational elements, are becoming increasingly popular in recent years. As complex systems themselves, CPSs are frequently used in complex applications such as smart power grids, transport systems, and financial infrastructure. Security is a critical and challenging aspect that needs more attention during CPS design, due to the extensive use of CPSs in applications. To address this, we discuss CPS security threats and investigate specific security measures that can be taken. This paper, firstly introduces the CPS architecture, which consists of a perception layer, a data transport layer, and an application control layer. We then outline security threats and measures taken to combat threats at each of the three layers. Finally, using the smart grid as an example, we present a short analysis of typical threats and measures to keep the smart grid cyber safe. In addition, we list differences between IoT security and CPS security to compare the two methods.